Perlindungan Hukum atas Desain Industri Berdasarkan Undang-Undang No 31 T Ahun 2000 - Ida Ayu Mas lndriani; Ni Made Jaya Senastri; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2021)
Intellectual property rights including industrial designs. The idea of ​​industrial design safety is based on the belief that human imagination, taste and initiative are closely linked to industrial design. The state grants protection against new industrial designs. The definition of the rule of law used in the legal protection of industrial designs is based on Law No. 31 of 2000. One of the components in this case is the protection of human rights which is the guideline for the legal protection of industrial designs. There are two forms of industrial design legal protection, which include preventive legal protection and repressive legal protection. This study aims to examine the form of legal protection for industrial designs based on Law No. 31 of 2000 and analyze the legal implications if the design rights holder does not register their industrial designs. This research was designed using normative research with a conceptual approach. The data used are primary and secondary data obtained through documentation and recording. The results of the study indicate that preventive legal protection is contained in the Act which is used to prevent violations and a description of the implementation of obligations while repressive legal protection is security in the form of sanctions for violations that have been committed. In view of this and considering the existence of protection in the form of the industrial design law, the designer can prevent the occurrence of plagiarism of his industrial design by registering his industrial design.